White matter abnormalities: Insights into the pathophysiology of major affective disorders - Serafini, Gianluca (Baishideng Publishing Group Inc, 2014)
The presence of white matter hyperintensities (WMHs) has been commonly associated with poor outcome in subjects with major affective disorders. Unfortunately, WMHs may be frequently confounded by the use of psychoactive medications and duration of illness. Although findings from the current literature are quite conflicting, we proposed that subjects with WMHs may be at higher suicidal risk when compared to other subgroups without. Based on the Fazekas modified scale, the severity of WMHs may serve as a trait marker of disease. Interestingly, the presence of WMHs may represent a neurobiological marker between the underlying vulnerability and clinical presentation of major affective disorders.